2007
DOI: 10.1021/ac0621470
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Detection in Laser-Induced Breakdown Spectroscopy

Abstract: Gated detection with intensified detectors, e.g., ICCDs, is today the accepted approach for detection of plasma emission in laser-induced breakdown spectroscopy (LIBS). However, these systems are more cost-intensive and less robust than nonintensified CCDs. The objective of this paper is to compare, both theoretically and experimentally, the performance of an intensified (ICCD) and nonintensified (CCD) detectors for detection of plasma emission in LIBS. The CCD is used in combination with a mechanical chopper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 13 publications
1
39
0
Order By: Relevance
“…linear CCD) or a gated (e.g. intensified CCD camera, or iCCD for short) detector is better in a LIBS setup [22,23]. It has been suggested that linear CCD spectrometers are more robust, and provide better S/N and sensitivity; however, their resolution is poorer in broadband configurations and they do not enable sub-μs gating.…”
Section: Spectrometers and Detectorsmentioning
confidence: 99%
“…linear CCD) or a gated (e.g. intensified CCD camera, or iCCD for short) detector is better in a LIBS setup [22,23]. It has been suggested that linear CCD spectrometers are more robust, and provide better S/N and sensitivity; however, their resolution is poorer in broadband configurations and they do not enable sub-μs gating.…”
Section: Spectrometers and Detectorsmentioning
confidence: 99%
“…1(a), a typical LIBS signal receiving system has three main parts, namely optical system, detector system and electronic system. In the initial optical system, a fundamental noise source is photon shot noise, which results from the random nature of photon emission [25]. Photon shot noise is random, with a Poisson distribution of the number of detected photons [26].…”
Section: Summary Of Noise In Libs Systemmentioning
confidence: 99%
“…This was qualitatively confirmed by the following simple phenomenological model describing the temporal evolution of the continuum intensity I cont =I C · exp(−t /τ C ) and of the line intensity I line =I L ·t · exp(−t /τ L ), where I C and I L are the intensities when the laser pulse reaches the sample at t = 0. This means that the Bremsstrahlung continuously decreases with time whereas the line intensity shows a maximum at a delay τ L [8][9][10][11][12]; then the SBR can be analytically calculated as:…”
Section: Optimization Of the Signal-to-background Ratiomentioning
confidence: 99%